1965
DOI: 10.2307/3798633
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction Studies on Penned White-Tailed Deer

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
2

Year Published

1984
1984
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(92 citation statements)
references
References 4 publications
3
87
2
Order By: Relevance
“…Verme (1965) found that the time for onset of estrus in white-tailed deer was slightly delayed when the level of nutrition was lowered before the normal time of estrus. Smith (1964Smith ( , 1965, on the other hand, found that nutritional deficiencies during the winter and spring, at the time of lambing in sheep, delayed the time for onset of estrus the following autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Verme (1965) found that the time for onset of estrus in white-tailed deer was slightly delayed when the level of nutrition was lowered before the normal time of estrus. Smith (1964Smith ( , 1965, on the other hand, found that nutritional deficiencies during the winter and spring, at the time of lambing in sheep, delayed the time for onset of estrus the following autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional demands of pregnant females increase throughout gestation, with most fetal growth (.90%) occurring during the last one-third of gestation (Moen 1978, Robbins and Robbins 1979, Pekins et al 1998. Inadequate nutrition during gestation may result in fetal loss (Verme 1965), low birth weight and reduced probability of survival of young (Keech et al 2000, Lomas and, and life-long consequences on the physical characteristics and quality of the individual (Hamel et al 2009, Monteith et al 2009). Extended duration of confinement on a traditional winter range can lead to depletion of available browse resulting in increased competition for limited forage (Nicholson et al 2006).…”
Section: Spring Migrationmentioning
confidence: 99%
“…In poor environments leading to substandard nutritional conditions, both fetal growth rates and birth weights are restricted [6,48,49]. Consequently, estimating fetal age by fetal weight needs to take it into account that the birth weight might be different dependent on the nutritional status of the population.…”
Section: Discussionmentioning
confidence: 99%